The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0013161x20936346
|View full text |Cite
|
Sign up to set email alerts
|

School Governance and Student Achievement: Cross-National Evidence From the 2015 PISA

Abstract: Although cross-national evidence suggests that decentralization of educational governance is positively related to student achievement, related research often fails to recognize the separate roles and influences of governments, school boards, principals, and teachers. We use data from the 2015 Programme for International Student Assessment to examine school leaders’ perceptions of governance arrangements across 68 countries and to assess whether differences in perceived governance patterns are significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…In contrast, leadership in Norway is characterized by democratic values and collaboration whereas Chinese principals lead top-down. Luschei and Jeong (2021) analyzed data from the PISA study 2015 to understand the relationship among school governance structures, leadership and student achievement. While the authors found a considerable range of decision-making authority at the school level, there was no significant correlation between the responsibilities of a principal and student achievement, even after controlling for leadership behavior.…”
Section: School Leadership and The Importance Of Contextmentioning
confidence: 99%
“…In contrast, leadership in Norway is characterized by democratic values and collaboration whereas Chinese principals lead top-down. Luschei and Jeong (2021) analyzed data from the PISA study 2015 to understand the relationship among school governance structures, leadership and student achievement. While the authors found a considerable range of decision-making authority at the school level, there was no significant correlation between the responsibilities of a principal and student achievement, even after controlling for leadership behavior.…”
Section: School Leadership and The Importance Of Contextmentioning
confidence: 99%
“…Teachers would be satisfied if they have autonomy or collaborate with peers in school under the distributed climate (Strong and Yoshida, 2014). Several empirical investigations have also confirmed that principals' leadership style is crucial for determining the degree of teacher autonomy and collective activities (Luschei and Jeong, 2021). For instance, using teachers' data from the 2013 TALIS, one study indicated that distributed leadership significantly impacted teachers' professional learning community and cooperation practices (Bellibaş et al, 2021).…”
Section: Distributed Leadershipmentioning
confidence: 99%
“…Despite the wide promotion of these efforts, studies have reported mixed effects of school autonomy on student achievement (e.g., Hanushek et al, 2013;Luschei & Jeong, 2020;Steinberg, 2014) and organizational dynamics (e.g., Ingersoll, 1996). In response, researchers argue that the strategic use of autonomy emphasizing the promotion of teaching and learning and the development of schools' capacity (instead of the structure itself) is necessary for principals to enact autonomy over school-level decision-making effectively (Honig & Rainey, 2012).…”
Section: School and Principal Autonomymentioning
confidence: 99%
“…The ways principals in this study negotiated their time and workload provides us a new and perhaps different type of opportunity to understand principal autonomy. Though school reforms have steered governance structures toward increasing school autonomy for decades (Kim & Yun, 2019;Luschei & Jeong, 2020), participants seemed to struggle with fully utilizing this autonomy regarding their inclinations to achieve what they believed and valued as educators and leaders. This was particularly true regarding these principals' time use and, despite a multitude of other responsibilities, their prioritization of attending to students who appeared to need additional care.…”
Section: Principal Autonomy As Partial and Boundedmentioning
confidence: 99%
See 1 more Smart Citation